2022
DOI: 10.1136/openhrt-2021-001801
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid and berberine, via Sirt1 and AMPK, may act as cell cleansing promoters of healthy longevity

Abstract: Ferulic acid, a bacterial metabolite of anthocyanins, seems likely to be a primary mediator of the health benefits associated with anthocyanin-rich diets, and has long been employed in Chinese cardiovascular medicine. In rodent studies, it has exerted wide-ranging antioxidant and anti-inflammatory effects, the molecular basis of which remains rather obscure. However, recent studies indicate that physiologically relevant concentrations of ferulic acid can boost expression of Sirt1 at mRNA and protein levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 168 publications
(173 reference statements)
1
10
0
1
Order By: Relevance
“…Moreover, AMPK increases fatty acid oxidation in the liver and decreases de novo fatty acid synthesis, cholesterol synthesis, and lipogenesis by inhibiting sterol regulatory element binding protein 1c (SREBF1), HMG CoA reductase (HMGCR), and Acetyl-coA carboxylase (ACACA). In agreement with our proposal, previous studies have shown that MA ingredients, including Apigenin, luteolin, quercetin, ferulic acid, chlorogenic acid, isoorientin, naringenin, and resveratrol, ameliorate hyperglycemia and hyperlipidemia through activation of the AMPK signaling pathway and SIRT1 ( Ong et al, 2012 ; Jin et al, 2015 ; Tsai et al, 2018 ; Joshi et al, 2019 ; DiNicolantonio et al, 2022 ). Our network analysis also revealed an increase in adiponectin and leptin production, which may activate AMPK signaling.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, AMPK increases fatty acid oxidation in the liver and decreases de novo fatty acid synthesis, cholesterol synthesis, and lipogenesis by inhibiting sterol regulatory element binding protein 1c (SREBF1), HMG CoA reductase (HMGCR), and Acetyl-coA carboxylase (ACACA). In agreement with our proposal, previous studies have shown that MA ingredients, including Apigenin, luteolin, quercetin, ferulic acid, chlorogenic acid, isoorientin, naringenin, and resveratrol, ameliorate hyperglycemia and hyperlipidemia through activation of the AMPK signaling pathway and SIRT1 ( Ong et al, 2012 ; Jin et al, 2015 ; Tsai et al, 2018 ; Joshi et al, 2019 ; DiNicolantonio et al, 2022 ). Our network analysis also revealed an increase in adiponectin and leptin production, which may activate AMPK signaling.…”
Section: Discussionsupporting
confidence: 93%
“…In this regard, it is noteworthy that both mTOR activation and FoxO1 inhibition were originally linked to loss of KRIT1 function and shown to be associated with increased cellular ROS levels and susceptibility to oxidative stress via downregulation of autophagy and antioxidant defenses [ 15 , 19 ]. On the other hand, both AMPK and Sirt1 are known to play a positive role in the maintenance of cellular homeostasis and antioxidant defenses by opposing the actions of the Akt/mTOR pathway and promoting autophagy [ 95 , 99 , 100 ]. However, while AMPK and Sirt1 cooperate in orchestrating FoxO1-mediated compensatory responses to transient metabolic and oxidative stress for the maintenance of cell functions, these responses may result in inefficiency in chronic stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the GO and KEGG enrichment assays revealed that biological processes were distinctly enriched in the positive regulation of tumor necrosis factor production, particularly the positive regulation of tumor necrosis factor superfamily cytokine production. More data have suggested that ferulic acid might inhibit autophagy-dependent cell proliferation in cancers ( 32 ) as well as inflammation-related SARS-CoV-2 infection ( 33 ). Following the use of the molecular docking analysis, we ultimately identified the core ferulic acid target proteins against OS and COVID-19, namely, STAT3, MAPK1, and PIK3R1.…”
Section: Discussionmentioning
confidence: 99%